Retear of anterior cruciate ligament grafts in female basketball players: a case series - Tanaka, Y.; Yonetani, Y.; Shiozaki, Y.; Kitaguchi, T.; Sato, N.; Takeshita, S.; Horibe, S. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2010)
Background Incidence of anterior cruciate ligament (ACL) injuries in young female basketball players is higher than that in male basketball players. Graft retears are more frequent with the increasing number of ACL reconstructions. The present study aimed to examine the incidence of retears in competitive female basketball players.